Lipid is absorbed in the stomach by epithelial neoplasms (adenomas and early cancers): a novel functional endoscopy technique - Ohtsu, Kensei; Yao, Kenshi; Matsunaga, Kazuhisa; Nagahama, Takashi; Kanemitsu, Takao; Matsushima, Yu; Yasaka, Motochika; Ono, Yoichiro; Fujiwara, Shoko; Hisabe, Takashi; Takaki, Yasuhiro; Hirai, Fumihito; Matsui, Toshiyuki; Hanada, Teruyo; Imamura, Kentaro; Tanabe, Hiroshi; Iwashita, Akinori; Shimokawa, Toshio (Endoscopy International Open, 2015)
Background and study aims: The authors have successfully demonstrated that the white opaque substance (WOS) identified in gastric epithelial neoplasms is an accumulation of minute lipid droplets on the epithelial neoplasm. It is not known whether the lipid droplets originate from externally ingested lipids (typically foods). The purpose of this study was to investigate whether the oral ingestion of foods containing emulsified fats increases the density of the WOS in epithelial neoplasms.Patients and methods: We examined 92 gastric epithelial neoplastic lesions in 89 patients. The patients were given emulsified fatty foods before the procedure, and magnifying endoscopy with narrow-band imaging (M-NBI) was used to image the lesions. An increase in WOS density after the ingestion of emulsified fatty foods was defined as a positive fat-loading test result.The patients were divided into the following groups: control group, no emulsified fat administered; group 1, fatty food administered 16 hours prior; group 3, fatty food administered both 16 and 4 hours prior. The proportion of positive fat-loading test results was determined in all groups.Results: The rates of positive fat-loading test results were as follows: control group, 9 %; group 1, 26 %; group 2, 52 %; group 3, 78 %. The increase in the rates of positive fat-loading test results in groups 2 and 3 relative to the rate in the control group was statistically significant (chi-squared test).Conclusions: This study demonstrated for the first time that the ingestion of external lipids causes lipid droplets to aggregate in situ on the gastric epithelial neoplasm. These results can be used to develop a novel functional endoscopy technique that harnesses the lipid absorption capacity of neoplasms.